2016
DOI: 10.1111/obr.12435
|View full text |Cite
|
Sign up to set email alerts
|

Preventing childhood obesity in Asia: an overview of intervention programmes

Abstract: The rapid economic growth in Asia in the past few decades has contributed to the global increase in childhood obesity prevalence. Yet, little is known about obesity prevention efforts in this region. This systematic review provides an overview of child obesity prevention programmes in Asia. Searches were performed in six electronic databases. Out of 4,234 studies, 17 were included, among them 11 controlled trials (of which five were randomized). Only one study was published before 2007. Identified studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
1
22
0
1
Order By: Relevance
“…Previous systematic reviews [59,60] have highlighted the importance of engaging and supporting parents in the promotion of children's healthy behaviours, however, health promotion efforts have tended to focus on school settings. A systematic review of existing intervention studies in Asia, reported that all but one study occurred in a schoolbased setting and all targeted children at school age or above [61]. In light of our findings and previous evidence [25] with regards to the impact of detrimental parental behaviours (e.g.…”
Section: Discussionsupporting
confidence: 67%
“…Previous systematic reviews [59,60] have highlighted the importance of engaging and supporting parents in the promotion of children's healthy behaviours, however, health promotion efforts have tended to focus on school settings. A systematic review of existing intervention studies in Asia, reported that all but one study occurred in a schoolbased setting and all targeted children at school age or above [61]. In light of our findings and previous evidence [25] with regards to the impact of detrimental parental behaviours (e.g.…”
Section: Discussionsupporting
confidence: 67%
“…The increasing prevalence of childhood adiposity has become a major global health challenge, and actions to reduce the prevalence of obesity in children and adolescents are urgently needed (4, 63, 64). Investigating risk factors associated with childhood obesity can help us to develop effective prevention interventions (65).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most of these studies were conducted in Europe or the USA, 9 and the findings may not be culturally appropriate to Asian populations. 10 Previous evidence from a large-scale birth cohort study in Singapore suggests that preschool-aged children in Singapore are less active and more sedentary when compared with Western countries. 11 Longer school hours and more emphasis on children's academic performance may partly explain these differences.…”
mentioning
confidence: 99%